"E-Recruitment Vs. Traditional Recruitment: The Impact of Social Media" - D Jogish, Ningambika G Meti, Manjunatha. S, Chandana T C, Udaya. S (Journal of Informatics Education and Research, 2024)
E-recruitment is a fairly recent phenomenon that brings challenges for hiring managers and candidates.HR professionals use online techniques like posting job openings on their own platforms, social media, or the web to identify possible applicants. Businesses and human resources specialists want to integrate e-recruitment into their employment processes since it is faster and more effective than traditional hiring methods. This study set out to ascertain the impact of social networks and whether the traditional employment procedure has lost value. The author believes that doing both qualitative and quantitative analysis was suitable to gain a complete insight of the topic matter. The author used secondary research to both confirm and contradict many of the conclusions of the empirical research allowing them to make judgments regarding the theories they had formed throughout their research. The study yielded several results, opening the door to suggestions for further investigation. There are several elements of traditional recruiting that never change, even though e-recruitment is the reality of the future for hiring. DOI: https://doi.org/10.52783/jier.v4i3.1393